2009
DOI: 10.1002/chin.200924080
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ZrOCl2 Catalyzed Baeyer Condensation: A Facile and Efficient Synthesis of Triarylmethanes under Solvent‐Free Conditions.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…More recently, the Baeyer condensation reaction has been conducted using microwave radiation. It was shown that yields of 70–96% were achieved with catalytic amounts of ZrOCl 2 , or p -toluene sulfonic acid, with no additional solvent required.…”
Section: Catalysis and Organic Synthesismentioning
confidence: 99%
“…More recently, the Baeyer condensation reaction has been conducted using microwave radiation. It was shown that yields of 70–96% were achieved with catalytic amounts of ZrOCl 2 , or p -toluene sulfonic acid, with no additional solvent required.…”
Section: Catalysis and Organic Synthesismentioning
confidence: 99%
“…Following the successful introduction of triazoles and thiazolidinones, microwave-assisted MCR reactions, inspired by the biological profile of triazoles, thiazolidinones, and in the continuation of our work on biologically active heterocycles [18][19][20][21][22][23][24][25][26][27][28][29] we have developed a series of novel triazole-linked thiazolidenone derivatives, we have investigated the application of microwave irradiation for the synthesis of our hybrid molecules and evaluated their anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the immense importance and varied bioactivities exhibited by triazolo-thiadiazines and thiadiazepines and in continuation of our work on biologically active heterocycles, [43][44][45][46][47][48][49][50][51] we were stimulated to integrate thiadiazines moieties in a triazole framework, since these systems possess well documented antimicrobial activity. In this connection, some bis-heterocyclic compounds such as bis-triazolo thiadiazines and triazolo-thiadiazepines have been synthesized and evaluated for their antibacterial and antifungal activity.…”
Section: Introductionmentioning
confidence: 99%